School Social Media Management as a Learning Resource to Develop Digital Literacy of Students at Tanjungsari 1 Elementary School Wonogiri Regency - Ganies Andhira Faza Perdana; Ratnasai Dyah Utama (FKIP - Universitas Riau, 2026)
The Industrial Revolution 4.0 era has shifted human life patterns towards a digital-based one, making digital literacy a crucial competency for students facing global competition. This study aims to describe the management and utilization of school social media as a learning resource in developing students' digital literacy at SD Negeri 1 Tanjungsari. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results show that school social media management is implemented through seven systematic stages, from planning to monitoring and evaluation. The use of social media as a learning resource is implemented through the planning, implementation, and evaluation phases of learning. The results of the analysis of students' digital literacy development show a high category in the cultural, cognitive, self-confidence, critical, and social responsibility indicators, while the constructive, communicative, and creative indicators are in the medium category. Although there are obstacles such as limited teacher digital competence, infrastructure, and internet access, it can be concluded that structured social media management is effective in supporting the improvement of elementary school students' digital literacy skills.